The preventive nature of the construction law in the scope of environmental protection - Smarż, Joanna (The Opole Studies in Administration and Law, 2025)
The environment is a common good that must be protected for future generations. Therefore, environmental protection is an important aspect taken into account by the legislator in a number of generally applicable regulations. The basic legal act in this area is the Environmental Protection Law. However, during the construction process, the provisions of the Construction Law, which strengthen and supplement the provisions of the Environmental Protection Law, are of particular importance. Therefore, it is worth analyzing the mutual relations between these regulations, which are in force simultaneously during the construction process. The thesis of the article is the statement that the provisions of the Construction Law are preventive in the field of environmental protection. The purpose of these regulations is toprevent activities that may have a negative impact on the environment during the construction process. Therefore, the provisions of the Construction Law apply from the stage of investment planning, through its implementation, into the use of completed facilities. In order to ensure proper environmental protection, these regulations will introduce stricter requirements for investments that may have a negative impact on the environment, protecting it. As the analysis of the above-mentioned regulations shows, environmental protection, within the scope regulated by the provisions of the Construction Law, is an indispensable element of the process of planning and implementing investments aimed at sustainabledevelopment, minimizing the negative impact on the environment and caring for natural heritage. Unfortunately, sometimes the provisions of both acts are not consistent with each other. An additional difficulty is that the provisions of the Construction Law and environmental protection are not the only regulations that should be taken into account during the implementation of a construction project. The number of regulations in force, depending on the type of investment, is significant, which makes it difficult for investors to apply themcorrectly. The dogmatic-legal method was used to amalyze the title issue.